1981
DOI: 10.1093/bja/53.3.267
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Three Doses of Ici 35 868 for Induction and Maintenance of Anaesthesia

Abstract: Three doses (1.5, 2.0 and 2.5 mg kg-1) of diisopropyl phenol (ICI 35 868) were compared for induction and maintenance of anaesthesia in healthy females undergoing short gynaecological procedures. Induction of anaesthesia was smooth and rapid. Cardiovascular changes (which were dose-dependent) included a decrease in arterial pressure and an increase in heart rate. These changes were magnitudes comparable to those reported for other induction agents. Recovery from the effects of the drug was rapid and uneventful. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
1

Year Published

1982
1982
2001
2001

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(19 citation statements)
references
References 4 publications
3
15
1
Order By: Relevance
“…did not affect the frequency of pain on injection, so it is probable that the reduced incidence in this study (12%) is related more to the site of injection than to the premedication with fentanyl. The fact that two patients out of 26 (8%) required a higher dose of disoprofol is in keeping with the findings of others (Rogers et al, 1980;Briggs et al, 1981;Major et al, 1981), who found that 2mgkg" 1 induced anaesthesia successfully in 90-100% of patients without unacceptable arterial hypotension or respiratory depression. They found l.Smgkg" 1 was unreliable and produced anaesthesia in only 25-70% of patients.…”
Section: Discussionsupporting
confidence: 88%
“…did not affect the frequency of pain on injection, so it is probable that the reduced incidence in this study (12%) is related more to the site of injection than to the premedication with fentanyl. The fact that two patients out of 26 (8%) required a higher dose of disoprofol is in keeping with the findings of others (Rogers et al, 1980;Briggs et al, 1981;Major et al, 1981), who found that 2mgkg" 1 induced anaesthesia successfully in 90-100% of patients without unacceptable arterial hypotension or respiratory depression. They found l.Smgkg" 1 was unreliable and produced anaesthesia in only 25-70% of patients.…”
Section: Discussionsupporting
confidence: 88%
“…Adequate facilities for artincial ventilation must be available, because although in the event of overdosage with an intravenous anaesthetic intermittent positive pressure ventilation will have no effect on the elimination of the drug administered, oxygenation and carbon dioxide removal must be ensured. Disoprofol (2,6 di-isopropylphenol presently solubilised in 16% cremophor EL) appeared a potentially suitable agent for total intravenous anaesthesia trials in the horse, due to its rapid onset of action, duration of effect due to rapid metabolism in man and other species, and apparent lack of cumulation (Adam et al, 1980;G~n, 1980;Ruther et al, 1980;Briggs et al, 1981;Major et al, 1981, Verniquet et al, 205. 1981Heneghan et al, 1982).…”
mentioning
confidence: 99%
“…A further potential advantage of the reduced doses of propofol required for induction of anaesthesia and insertion of the laryngeal mask may be improved cardiovascular stability and reduced respiratory depression. It is known that the extent of the blood pressure reduction seen with propofol is dose dependant [26,27]. This present study did not aim to examine this aspect.…”
Section: Discussionmentioning
confidence: 94%